Medieval popular culture (Problems of belief and perception) - Aron Gurevich (Cambridge Univ. Press, 1987)
The book attempts to reconstruct the beliefs and perceptions of the "silent majority" of medieval men and women from the writing of clerical authors. By scrutinizing the lives of saints, micracle stories, descriptions of fantastic travels, penitential literatur, catechisms and similar genres, from the fifth to the fifteenth centuries, the book identifies elements of popular culture that found their way into Latin literature through mutual interaction between author and audience. It offers a fresh and original insight into the world of the coomon man, his everyday habits, beliefs and behaviour